Maintenance of automatic valve parts in soy blending tanks using the reliability centred maintenance method at PT KHAI - Wiguna, Adityanata; Kusnadi, Kusnadi; Nugraha, Asep Erik (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
In the manufacturing industry, effective machine maintenance is essential to ensure production continuity and prevent downtime. PT KHAI faces performance degradation and damage to the automatic valve parts in its soy blending tanks, leading to significant production losses. This study analyzes the maintenance of these components using the Reliability Centred Maintenance (RCM) method. The novelty of this research lies in its specific application to piston-actuated butterfly valves within the liquid handling systems of the food processing industry, a specialized area that remains under-explored compared to heavy machinery or power plant sectors. The methodology involves system identification, Failure Mode and Effect Analysis (FMEA), Logic Tree Analysis (LTA), and Task Selection. The results identify critical failure components, including actuators, bearings, seals, packing valves, solenoid valves, limit switches, and control systems. The proposed maintenance strategy consists of time-directed tasks for four components, condition-directed for one component, and finding failure for three components. In conclusion, this study provides a new framework for mitigating hidden failures in automated actuation systems, offering a replicable maintenance model for ensuring high-hygiene production efficiency in the food industry.